Conduction defects and arrhythmias in mdx mice are not associated with a degeneration of the cardiac Purkinje network - Vahdat, Juliette; Sauer, Jakob; Marksteiner, Jessica; Hilber, Karlheinz; Miquerol, Lucile (Frontiers in Physiology, 2025)
Duchenne muscular dystrophy (DMD) is a severe X-chromosomal disease characterised by progressive muscle weakness and degeneration. Cardiac involvement is inevitable in DMD patients and ventricular arrhythmias are a high-risk factor for mortality in these patients. Ventricular arrhythmias are often triggered by a dysfunctional ventricular conduction system, which serves as an electrical circuit in the heart to ensure the synchronization of the heartbeat. This system includes Purkinje fibers which are susceptible to degeneration in DMD patients, leading to cardiac conduction disorders. To unravel whether a defective ventricular conduction system may account for arrhythmogenesis in a DMD mouse model, we performed a longitudinal study of the cardiac electrical activity in mdx mice. ECG recordings showed a progressive increase in PR interval over time and a prolonged QRS in mdx compared to wild-type (WT) mice. At baseline, only mdx mice presented premature ventricular complexes (PVC), and a greater prevalence of PVC was observed after β-adrenergic stimulation in these mice. These conduction defects and arrhythmias occurred while no defects in the morphology and maturation of the Purkinje fiber network were observed. However, mdx mice had a larger heart and showed signs of fibrosis and hypertrophy. Furthermore, conduction defects in mdx mice were associated with ventricular dyssynchrony and sodium current (INa) reduction in ventricular myocytes and Purkinje fibers. Altogether, these data demonstrated that mdx mice develop a progressive arrhythmogenic cardiomyopathy in association with INa loss, ventricular fibrosis but without degeneration of the ventricular conduction system.